PTU-037 Improving Acute upper GI Bleeding Services in a District General Hospital. (4th June 2013) - Moffat, D R; Gooding, I; Sundaralingam, A; Wong, M T; Shaw, K
Abstract : Introduction: Colchester General Hospital (CGH) serves a population of 360, 000. Approximately 300–350 patients present with acute upper gastrointestinal bleeding (UGIB) per annum. NICE guidelines recommend gastroscopy (OGD) within 24 hours of presentation. In 2009, there was no dedicated provision for OGD for UGIB cases. Only 15% of patients at CGH met the 24 hour target. To improve performance, we introduced a new Early Morning Bleeding (EMB) OGD list. The EMB list providesprotected endoscopy slots between 08:00 to 09:00. This 5 days week service was introduced in July 2009. To further improve our performance we extended this to an EMB list 7 days a week in November 2011. Data was collected for 2011 and 2012 to assess the outcomes of our performance. Methods: Data was collected for all UGIB cases over the same three-month period (March- May) in 2009, 2011 and 2012. Cases were identified from investigation request forms. Inclusion for the analysis was the OGD indication being either for haematemesis, melaena or unexplained haemoglobin drop. For each case we obtained the admission date and time, OGD date and time and the length of hospital stay (LOS) from hospital databases. The endoscopic diagnosis and treatment information was also collected. Patient s admitted for UGIB were separated from patients developing bleeding after admission, by the use of electronic discharge summaries and patient records. Wait from admission to OGD and LOS were calculated for patients admitted for UGIB. Surgical theatre logbooks were consulted to identify emergency out-of-hour OGDs for the period 2007–2012. Wilcoxon rank sum tests were used to compare wait times to OGD and LOS. Results: Conclusion: Providing an EMB list 7-days is an effective method to improve services. Compliance with 24hr target guidelines improved from 14.8% to 75%. LOS was reduced by 50%. Providing a 5-day service resulted in substantial improvements but did not achieve adequate compliance. Whilst our study is too small to assess any impact on mortality, the reduction in emergency out-of-hours procedures with a 7-day service indicates an improvement in patient safety. The EMB system is relatively cheap: during the week no new resources are required. We had only to staff new lists at weekends. The system ensures that most procedures are performed by consultant gastroenterologists experienced in endoscopic therapy for UGIB. The marked reduction in emergency cases suggests that any further improvements in outcomes from providing a (much more expensive) 24/7 service are unlikely to be cost effective. Disclosure of Interest: None Declared